Egg Quality Traits of Layers Fed Sugarcane Press Residue with Biotechnological Agents - Suresh, B.N.; Reddy, B.S.V.; B.H, Manjunatha Prabhu; Suma, N. (International Journal of Poultry Science, 2009)
An experiment was conducted to investigate the influence of inclusion of Sugarcane Press Residue (SPR) as a feed ingredient in layer diets on the qualities of the egg. Three experimental diets were formulated by incorporating SPR at 0, 5 and 10%. Another set of nine diets were prepared by supplementing each diet with either lipid utilizing agents (lipase and lecithin) or NSP degrading enzymes or together. Each of the twelve diets was offered to triplicate groups of 4 laying birds each. The trial lasted for 84 days divided in to three periods of 28-days each. The egg quality characteristics such as egg shape index, albumen index, Haugh unit scores, yolk index and yolk colour was statistically similar (p>0.05) among different treatments at different stages of experiment. However, the influence of different treatment diets on egg shell thickness was significant (p